Influence of polymerization on the synthesis of SrTiO3: Part I. Characteristics of the polymeric precursors and their thermal decomposition - Leite, E. R.; Sousa, C. M G; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier, 1995)
The influence of polymerization on the thermal decomposition of polymeric precursors and phase formation was investigated during synthesis of SrTiO3. The precipitation of polymeric precursor in acetone produced a more thermal stable precursor with lower weight loss during decomposition. This more stable precursor retarded the formation of the SrTiO3 phase. From thermal analysis, XRD and FT-IR the presence of an intermediate phase during decomposition of the precursors was observed. This is a mixed (Sr,Ti) carbonate phase with the proposed composition of Sr2Ti2O5.CO3. © 1995.